1998
DOI: 10.1111/j.1748-5827.1998.tb03624.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of ticarcillin in the management of canine otitis externa complicated by Pseudomonas aeruginosa

Abstract: Twelve dogs were referred with purulent and proliferative otitis externa. Prior treatment included fluoroquinolones, glucocorticoids and polyvalent ear drops over seven days to five months. In all cases the vertical and horizontal ear canals were inflamed and thickened, with ruptured tympanic membranes in four cases. No abnormalities were seen on radiography of the osseous bullae. Numerous rod bacilli and degenerate neutrophils were seen on cytology. Pseudomonas aeruginosa resistant to fluoroquinolones and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 5 publications
0
28
0
3
Order By: Relevance
“…Additional unpublished data provided by the authors were included in the analysis of one trial 17 . Nine studies were written in English 17–25 and two in French 15,16 The 10 trials reported data on 162 patients and 13 different pharmacological interventions. Three were controlled trials lacking randomization (quality of evidence: grade B) 15,16,23,25 and the others were open, uncontrolled studies (grade C) 17–22,24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional unpublished data provided by the authors were included in the analysis of one trial 17 . Nine studies were written in English 17–25 and two in French 15,16 The 10 trials reported data on 162 patients and 13 different pharmacological interventions. Three were controlled trials lacking randomization (quality of evidence: grade B) 15,16,23,25 and the others were open, uncontrolled studies (grade C) 17–22,24 .…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were written in English 17–25 and two in French 15,16 The 10 trials reported data on 162 patients and 13 different pharmacological interventions. Three were controlled trials lacking randomization (quality of evidence: grade B) 15,16,23,25 and the others were open, uncontrolled studies (grade C) 17–22,24 . Data from five of the trials were extracted from larger studies evaluating the efficacy of treatments for otic infections caused by various bacteria, yeast or parasites 19,20,22–24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to assess how often it is possible to make a specific primary diagnosis, as little data are available. A primary cause was identified in 8/12 cases of chronic, proliferative Pseudomonas otitis 40 and Griffin asserts that, 'In the majority of chronic ear cases I can find historical or physical evidence of the primary disease.' 18 It seems likely that the primary cause can be found in a reasonable number of cases and that predisposing, secondary and perpetuating causes can be identified and controlled in most.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…30 In humans, the drug is excreted primarily unchanged in the urine. 1 Although it has been used for a wide variety of human infections, 1 its veterinary use has been limited primarily to dogs 7,9,16,27 and horses, 20,[23][24][25]28 with investigational use in dairy cows 15 and sheep. 4 Ticarcillin and carbenicillin may have very similar efficacies, 14 except that ticarcillin has increased activity against Pseudomonas aeruginosa, gramnegative bacilli, and less activity against gram-positive cocci.…”
Section: Introductionmentioning
confidence: 99%